2011
DOI: 10.2147/hiv.s15532
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii IgG antibody in HIV-infected patients at the Lagos University Teaching Hospital

Abstract: BackgroundToxoplasmosis is caused by infection with a ubiquitous intracellular protozoan parasite, Toxoplasma gondii. With the advent of the HIV pandemic in Nigeria, toxoplasmic encephalitis has become one of the more frequent opportunistic infections and the most commonly implicated cause of focal brain lesions complicating the course of AIDS.ObjectivesThis study was conducted to compare the pattern of seroprevalence of T. gondii (Toxo-IgG) antibodies among HIV-infected persons presenting with neurological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 14 publications
3
16
2
Order By: Relevance
“…Other studies [19] showed that 79.0% and 79.4% of these patients had CD4 + counts,<100 and<150 cells/μl, that are contrary to the findings in this study. Thus, CD4 + cell counts serve as a reliable indicator for possible toxoplasmosis, and also contribute significantly to protection against chronic T. gondii infections via their role as helper cells for antibodies production.…”
contrasting
confidence: 99%
“…Other studies [19] showed that 79.0% and 79.4% of these patients had CD4 + counts,<100 and<150 cells/μl, that are contrary to the findings in this study. Thus, CD4 + cell counts serve as a reliable indicator for possible toxoplasmosis, and also contribute significantly to protection against chronic T. gondii infections via their role as helper cells for antibodies production.…”
contrasting
confidence: 99%
“…In the United States, toxoplasma seroprevalence varies from 3% to 30%, whereas in France 73%–90% of the population is infected [10]. Reported seroprevalence rates were varied from 13–31% in the general population, and 45–68% in HIV patients in studies from several developing countries [8], [27], [28]. In our study, 78% of patients had detectable toxoplasma IgG, but this does not reflect the seroprevalence in the general population or among unselected HIV-infected patients, as only meningitis patients were examined.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of cerebral toxoplasmosis is supported by positive serology and neuroimaging with CT or MRI. Toxoplasma seropositivity rates in HIV patients varies in different populations from 10 to 50%, with the highest incidence occurring in Africa [5] . Toxoplasma immunoglobulin G (IgG) antibodies have a high sensitivity, with 97% of patients with cerebral toxoplasmosis having a positive result [6] .…”
Section: Discussionmentioning
confidence: 99%